Simulation analysis of zinc ablation process and mass by intense pulsed ion beam irradiation. (21st June 2017) - Zhang, J.; Zhong, H.W.; Yu, X.; Shen, J.; Liang, G.Y.; Cui, X.J.; Zhang, X.F.; Zhang, G.L.; Yan, S.; Le, X.Y.
Abstract: As the strong thermal effect in the surface, intense pulsed ion beam (IPIB) has been extensively used in material surface modification. The ablation is an important part in the interaction process between IPIB and material. In order to investigate the ablation mechanism, combined with IPIB dynamic energy spectrum and infrared imaging diagnostic results, a two-dimensional axisymmetric heat conduction model considering the effect of ablated material was constructed to describe the ablation process and calculate the lost mass of the targets. The influences of beam parameters and ablated matter on the ablation rate were discussed. The experimental and simulative results of ablation threshold and mass were compared.